ملامح من الحياة الاقتصادية بوارجلان من خلال كتاب المعلّقات لمجهول (ق 3-6ه/6-12م) - يحياوي سعد; غرايسة عمار (University of Eloued جامعة الوادي, 2024)
تتلخص فكرة المقال بدراسة بعض الجوانب من الحياة الاقتصادية بوارجلان على ضوء ما ورد في كتاب المعلّقات لمؤلّف مجهول من علماء القرن السادس الهجري، حيث أورد في كتابه العديد من المعلومات المتعلقة بحاضرة وارجلان، قلّما نجدها في المصادر الأخرى والتي أرخت لهذه الحاضرة. وفي هذا الصدد نحاول أن نسلط الضوء في هذا البحث على إبراز بعض الجوانب من الأنشطة الاقتصادية التي كان يمارسها المجتمع الوارجلاني في حياته اليومية ما بين القرنين3-6ه/6-12م التي تعرض لها المؤلِّف خاصة ما تعلق منها بالنشاط الفلاحي والتجاري والمكاييل المنتشرة في الأسواق.The idea of the article revolves around studying some aspects of the economic life in Warqlan in light of what is mentioned in the book "AlMu'allaqat" by an unknown author, who is a scholar from the 6th century Hijri. Were he mentioned in his book many pieces of information related to the city of Warqlan, rarely found in other sources, which shed light on the history of this city. In this context, the research attempts to highlight some aspects of the economic activities practiced by the Warqlan society in its daily life between 3-6 AH/6-12 CE The author particularly focuses on agricultural and commercial activities, as well as the prevalent measurement units in the markets during that period.
Keywords: ملامح; الحياة الاقتصادية; وارجلان; المعلّقات; مجهول; Features; Economic Life; Warqlan; Al-Mu'allaqat; Unknown